2008
DOI: 10.1007/s10955-008-9529-8
|View full text |Cite
|
Sign up to set email alerts
|

Large Scale Dynamics of the Persistent Turning Walker Model of Fish Behavior

Abstract: This paper considers a new model of individual displacement, based on fish motion, the so-called Persistent Turning Walker (PTW) model, which involves an Ornstein-Uhlenbeck process on the curvature of the particle trajectory. The goal is to show that its large time and space scale dynamics is of diffusive type, and to provide an analytic expression of the diffusion coefficient. Two methods are investigated. In the first one, we compute the large time asymptotics of the variance of the individual stochastic tra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
142
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(149 citation statements)
references
References 45 publications
(62 reference statements)
4
142
0
2
Order By: Relevance
“…In addition to offering a more robust model of zebrafish locomotion, the inclusion of jumps is intended to capture sudden and abrupt changes in direction [5,23]. Similar to previous studies on individual animal motion [32,33], zebrafish turn rate is found to have correlated time increments. Unlike the smooth trajectories seen in representative traces of larger fish, such as the barred flagtail fish in [33], the direction of motion of zebrafish is found to change abruptly.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…In addition to offering a more robust model of zebrafish locomotion, the inclusion of jumps is intended to capture sudden and abrupt changes in direction [5,23]. Similar to previous studies on individual animal motion [32,33], zebrafish turn rate is found to have correlated time increments. Unlike the smooth trajectories seen in representative traces of larger fish, such as the barred flagtail fish in [33], the direction of motion of zebrafish is found to change abruptly.…”
Section: Discussionmentioning
confidence: 60%
“…Recent works have also addressed animal movement at the individual level using correlated random walks (CRWs) [26,[30][31][32][33]. In these studies, successive steps taken by the animal are assumed to be correlated, as in the persistent random walker (PRW) model proposed in [30] to study ant displacement and the CRW model proposed in [31] to study caribou movement.…”
Section: Introductionmentioning
confidence: 99%
“…This is a contrasted difference from Cucker-Smale's original proof [2,3] and its modified approach in [8] using a bootstrapping argument. We refer to Degond and Motsch's works [4,5,6] for recent kinetic description of Viscek type model for flocking.…”
Section: Introductionmentioning
confidence: 99%
“…Mathematical models for swarming, schooling, and other aggregative behavior in biology have given us many tools to understand the fundamental behavior of collective motion and pattern formation that occurs in nature [10,6,2,26,25,14,7,13,27,19,33,32,23,11,17,37,38,34,36,9,15,29,21,20,24,8]. One of the key features of many of these models is that the social communication between individuals (sound, chemical detection, sight, etc...) is performed over different scales and are inherently nonlocal [11,22,2].…”
Section: Introductionmentioning
confidence: 99%